The synthesis and some transition metal complexes of tolyl N-imidazolylmethyl ketoxime - Cukurovali, A; Tas, E; Ahmedzade, M (Taylor & Francis Inc, 1997)
p-Tolyl N-imidazolylmethyl ketoxime was synthesized by the reaction of o,p-tolyl N-imidazolylmethyl ketone and hydroxylamine hydrochloride. This compound was used as a complexing agent for Cd(II), Co(II), Cu(II), Ni(II ), and Zn(II). The ligand and complexes were characterized by elemental analyses, infrared and UV-VIS spectra, H-1 NMR, magnetic measurements, thermogravimetric analyses (TGA) and differential thermal analyses (DTA).
Keywords: Nickel(Ii) Complexes; Cadmium(Ii); Copper(Ii); Chemistry; Ligands; Oxime